Comparative Study of Keypoint Detection and ArUco Marker Methods for Optical 6D Pose Estimation in Electronics Packaging - Janisch, Lucas; Schulz, Daniel; Schmidt, Alexander; Kamps, Tobias; Reisch, Raven; Franke, Jörg (2024 IEEE 20th International Conference on Automation Science and Engineering (CASE), 2024)
The push for miniaturization and functional integration in electronics packaging is driving the adoption of increasingly complex three-dimensional designs, necessitating advanced optical 6D Pose Estimation techniques for precise automated manufacturing. This study covers the development, investigation, and comparison of two distinct optical approaches aimed at achieving precise pose detection with six degrees of freedom (6-DoF) of electronic components, in particular of Direct Bonded Copper substrates. One method involved using laser-engraved optical markers (specifically ArUco Markers), while the other relied on Keypoint Detection, utilizing YOLOv8 and Mask R-CNN trained on both real and synthetic data. Performance evaluation of these techniques was conducted by engineering a novel vision setup designed to maintain precise control over lighting conditions while facilitating accurate pose adjustments of the probe in six dimensions relative to the camera. The analysis revealed that the Keypoint Detection method, particularly with YOLOv8, exhibited superior accuracy in translation along the x- and y-directions, as well as rotation around the x- and y-axes. Conversely, the marker-based approach demonstrated significantly higher accuracy in translation in the z-direction and rotation around the z-axis. Through a qualitative analysis coupled with extensive quantitative evaluation, the study reveals the strengths and weaknesses of 6D Pose Estimation methods, particularly when applied to miniature copper components.
CRIS-Team Scopus Importer:2024-11-15

Continuous Improvement of the Screen printing Process of Magnetic Sheets for Electric Machines by Statistical Design of Experiment - Schmidt, Alexander; Wieprecht, Nico; Thamm, Julian; Kühl, Alexander; Franke, Jörg (Lecture Notes in Mechanical Engineering, 2023)
Electric machines are an essential element to the electrification of industry and mobility for achieving a sustainable economy. Particularly important are the resource-efficient production of stator and rotor sheet packages and the reduction of iron losses during operation. The screen printing technology enables the production of very thin magnetic sheet laminations in near net shape geometry and thereby minimization of material waste in production. Simultaneously the efficiency of electric motors in use will be increased by reduced eddy current and hysteresis losses due to decreasing sheet thickness and avoided mechanical stress in the manufacturing process. In addition, screen printing enables multi-material components and variable alloy compositions. This paper presents the requirements of the screen printing process for magnetic sheets and identifies the relevant influencing factors and printing parameters to achieve the product specifications in multiple iterations and using universal statistical design of experiments methods. The target parameters investigated are cycle-time, green part weight, roundness, and layer thicknes
Keywords: Additive Manufacturing; Electric Motor; Magnetic Sheets; New Materials; Resource-efficient Production

Development of Magnetic Sheets for CO2 Efficient Electric Drives Using an Additive Manufacturing Approach - Schmidt, Alexander; Ziegler, Marco; Kühl, Alexander; Franke, Jörg (Springer Science and Business Media Deutschland GmbH, 2023)
Keywords: Magnetic Sheets; New materials; Electric Motor; Electrical Steel; Sustainable Manufacturing; Additive Manufacturing

Experimental Setup of a Process Chain for Contacting Litz Wires for Electrical Drives - Riedel, Andreas; Seefried, Johannes; Schmidt, Alexander; Kühl, Alexander; Franke, Jörg (30th International Conference on Electrical Contacts, ICEC 2020 - Proceedings, 2021)
The main objective in the development of electric drives is the continuous effort to increase the performance. One possibility to achieve this is the use of shaped litz wires. However, shaped litz wires present major challenges regarding the contacting process. In the preparation of the contacting process, the individual conductors of the litz wires must be completely stripped without residues and brought into a defined geometry. This preliminary process step is also known as compacting. The compacting process is the basis for the subsequent contacting of the litz wires with each other or with contact elements. One process for contacting the litz wires is laser beam welding. In the context of this publication, the process chain consisting of ultrasonic compacting and laser beam welding is evaluated. The focus is put on the possible variations of the litz wire topologies, which differ in single wire diameter, number of wires and degree of insulation. Depending on this, parameters for the two processes are elaborated. To evaluate the results, electrical and mechanical testing of the litz wire connections is carried out. In addition, different approaches for the qualification of the compaction quality, in particular the evaluation of insulation residues, are considered.
CRIS-Team Scopus Importer:2023-03-07

Multi-objective parameter optimization for stacking and sintering of screen-printed magnetic sheets - Schmidt, Alexander; Wieprecht, Nico; Weinrich, Tim; Franke, Jörg; Kühl, Alexander (Production Engineering, 2023)
Screen printing enables the production of very thin magnetic sheet laminations in near net shape geometry. This minimizes material waste in production and simultaneously reduces losses during machine operation and in-creases geometric design freedom. The subsequent sintering process step is particularly relevant, since the geometrical and magnetic properties are defined, and relevant process costs are caused by the heat treatment. This paper presents the requirements of the debinding and sintering process for magnetic sheets and identifies relevant influencing factors to achieve defined product specifications in multiple iterations, using design of experiments. It focuses on the influencing factors furnace atmosphere, sintering temperature, holding time and stacking height and their impact on the magnetic and geometric properties of sintered magnetic sheets.<br
Keywords: Electric motor; Heat treatment; Magnetic sheets; New materials; Sintering; Soft magnetic materials

Process Development of Screen-Printed Magnetic Sheets for Electric Machines via Statistical Design of Experiments - Schmidt, Alexander; Wieprecht, Nico; Schlichting, Johannes; Denneler, Stefan; Franke, Jörg; Kühl, Alexander (Metals, 2023)
Electrical machines play a major role in achieving a more sustainable economy by driving the further electrification of industry and transportation. To enhance the electric motor productivity during production and the efficiency during operation, it is essential to maximize the material yield rate during the production of stator and rotor sheet stacks and reduce iron losses during operation. Screen-printing technology can help to achieve these goals by producing thin magnetic sheet laminations in near-net-shape geometry, resulting in minimum material waste during production. Moreover, reducing the sheet thickness decreases the eddy current losses and avoids mechanical stress during manufacturing, leading to improved motor efficiency. Additionally, screen printing facilitates the production of multi-material components and variable alloy compositions. This study aims to identify the relevant factors and printing parameters so that screen-printed magnetic sheets can achieve product specifications. A method involving the statistical design of experiments is performed in several iterations to investigate the target parameters of the print cycle time, green part weight, shape integrity and layer thickness, and to analyze the main interdependencies. The results of this study provide valuable insights into optimizing the screen-printing process for soft magnetic sheets, enabling the production of efficient electric motors while reducing material scrap.<br
Keywords: additive manufacturing; electric motor; magnetic sheets; new materials; resource efficient production; screen printing; stator core

Systematic Qualification of Layer Thickness, Roundness and Defects of Screen-printed Magnetic Sheets - Schmidt, Alexander; Wieprecht, Nico; Cosack, Alexander; Janisch, Lucas; Franke, Jörg; Kühl, Alexander (2023 13th International Electric Drives Production Conference (EDPC), 2023)
Screen printing offers the potential to produce near net shape and ultra-thin magnetic sheets for electrical machines. This is accompanied by significant potential for increasing performance. In this publication, the influence of various parameters on the geometric green part properties of screen-printed magnetic sheets is systematically analyzed by statistical design of experiment. The factors iron paste, design, substrate carrier and squeegee speed on the quality characteristics layer thickness, roundness, defects, and cycle time are considered. The aim of the investigation is to determine the main influencing factors and interactions on the target variables and the subsequent derivation of suitable parameter combinations by target variable optimization.<br
Keywords: Printing; Electric potential; Systematics; Shape; Production; Magnetic analysis; Substrates; Additive Manufacturing; Electric Motor; Magnetic Sheets; New Materials; Screen Printing